Diminished accuracy of biomarkers of fibrosis in low replicative chronic hepatitis B - Faisal M. Sanai; Taha Farah; Khalid Albeladi; Faisal Batwa; Yaser Dahlan; Mohammed A. Babatin; Hamad Al-Ashgar; Hadeel AlMana; Khaled S. Alsaad; Khalid AlSwat; Abdulrahman Aljumah; Ibrahim H. AlTraif; et al. (BMC Gastroenterology, 2017)
Abstract Background We evaluated the diagnostic accuracy of aspartate aminotransferase (AST)-to-platelet ratio index (APRI), fibrosis-4 index (FIB-4), AST/alanine aminotransferase (ALT) ratio (AAR), and age-platelet index (API) for significant fibrosis (Metavir F2–4) in low-replicative (HBV DNA <20,000 IU/mL) chronic hepatitis B virus (HBV) patients. Methods The sensitivity, specificity, and area under the receiver-operating characteristic curve (AUROC) of HBeAg-negative, low-replicative (n = 213) and high-replicative (HBV DNA ≥20,000 IU/mL, n = 153) patients was assessed. Results Overall, 113 patients (30.9%) had F2–4 fibrosis. Of the low and high-replicative patients, 40 (18.8%) and 73 (47.7%) had F2–4, respectively (P < 0.0001). APRI ≥0.5 less frequently identified F2–4 fibrosis in low vs. high-replicative patients (48.7% vs. 69.6%, P = 0.032) and AAR identified it more frequently in low-replicative patients (37.5% vs. 19.4%, P = 0.037). FIB-4 and API were not different (P > 0.05) for identifying F2–4 fibrosis in low and high-replicative patients. Higher specificities were seen at the lowest cut-offs in low vs. high-replicative states for APRI (≥0.5, 98% vs. 68.9%), AAR (84.3% vs. 76.6%), FIB-4 (≥1.45, 97.5% vs. 87.8%) and API (>4, 94.8% vs. 93.8%). At ROC-defined thresholds, APRI (≥0.33), AAR (≥0.93), FIB-4 (≥0.70) and API (>2) showed greater AUROCs for F2–4 diagnosis in low replicative (0.80, 0.62, 0.81 and 0.71, respectively) vs. high-replicative patients (0.73, 0.52, 0.67 and 0.69, respectively). Conclusion All 4 biomarkers in both, low and high-replicative HBV demonstrate modest accuracy for fibrosis diagnosis at conventional cut-offs. Lowering the cut-offs may increase the diagnostic relevance of these biomarkers, particularly for APRI and FIB-4 in low-replicative disease.